Living Beyond the Diagnosis: The Emotional and Social Journeys of People Living with HIV/AIDS – A Scoping Review - Deviantony, Fitrio; Ashari, Muhammad; Aindani, Rafelina Putri; Ramadina, Putri Dwi (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2025)
Individuals living with HIV/AIDS encounter a range of psychosocial issues that significantly impact their quality of life. Among these issues, stigma and mental health are critical components in understanding the overall well-being and treatment adherence of people living with HIV/AIDS (PLWHA). The integration of mental health support into HIV care is emphasized as a vital strategy for enhancing the quality of life for this population. The study aims to explore the psychosocial challenges faced by PLWHA in Indonesia and underscores the imperative of incorporating mental health assistance into HIV care frameworks. A literature review was conducted, examining studies published between 2020 and 2024. Relevant articles were sourced from databases such as Google Scholar and PubMed, utilizing keywords including